2020
DOI: 10.20525/ijfbs.v9i4.910
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Debt and Financial Performance of Small and Medium Scale Enterprises in Buganda Region, Uganda

Abstract: Short-term debt is regarded as an important source of financing for Small and Medium-sized enterprises (SMEs). This is because it can be easily accessed and useful during times of emergent working capital shortage. However, short-term debt is the least researched among the components of capital structure, which explains why its contribution to the financial performance of small and medium-sized businesses still lacks empirical validation especially in the Ugandan context. This paper sought to determine the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In addition, the type of corporate financial performance can be divided into short-term financial performance and long-term financial performance. Specifically, corporate short-term financial performance shows the past financial situation and present financial situation of the corporation (Mugisha et al, 2020). It mainly focuses on short-term capital flows, profit status and debt solvency.…”
Section: Corporate Financial Performancementioning
confidence: 99%
“…In addition, the type of corporate financial performance can be divided into short-term financial performance and long-term financial performance. Specifically, corporate short-term financial performance shows the past financial situation and present financial situation of the corporation (Mugisha et al, 2020). It mainly focuses on short-term capital flows, profit status and debt solvency.…”
Section: Corporate Financial Performancementioning
confidence: 99%
“…According to a recent study (Ombongi & Long, 2018), there is a clear link between SMEs' financial performance and the independent variables of labor expenses, bank credit, technology costs, GDP, and growth in the number of SMEs. The research by Mugisha, Omagwa, and Kilika (2020) showed that short-term debt has a negative and significant impact on SMEs' financial performance. (Wambua, 2019), study concluded that debt financing negatively and significantly affect financial performance of SMEs.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Like other regions, East Africa is facing challenges in the private sector where 70% of private companies collapse within 24 months due to poor financial performance, and Uganda tops countries with the highest rate (30%) of failing businesses (Orobia et al, 2020). Despite Government efforts to cushion private entities against financial shocks through subsidized lending, Uganda witnessed large-scale corporate failures where international and indigenous companies have since collapsed consequent to poor financial performance (Mugisha et al, 2020). The poor financial performance of private companies is likely to have drastic effects on the country's economic development if not checked.…”
Section: Introductionmentioning
confidence: 99%